Cross‐Cultural Validity of Bowen Theory in Southern European Countries. Issue 4 (10th December 2019) - Lampis, J.; Rodríguez‐González, M.; Cataudella, S.; Relvas, A. P.; Neophytou, K.; Agus, M.
Abstract : We present a comparison between Italy, Spain, Greece, and Portugal to test the cross‐cultural validity of the Differentiation of Self Inventory Revised (DSI‐R) Scales of emotional cut‐off (EC) and emotional reactivity (ER). Our study focuses on the importance of in‐depth analyses of the differentiation of self‐constructs from a cross‐cultural perspective and reflects on the possibility of conceptualising the universality of Bowen theory in southern European countries. The study involved 1, 807 healthy individuals. All participants completed the DSI‐R (Skowron & Schmitt, 2003). It was found that the measurement models had a suitable fit for each country group. Nevertheless, in our study, the two DSI‐R subscales, ER and EC, highlighted a weak invariance, specifically demonstrating only the invariance of the pattern factor loadings and the magnitude of factor loadings in the four samples. The empirical and clinical implications of these data are discussed.